Bat echolocation-inspired algorithms for global optimisation problems - Nafrizuan, Mat Yahya (Penerbit UMP, 2017)
Optimisation according to the definition of Merriam-Webster Dictionary is an act, process, or methodology of making something (as a design, system, or decision) as fully perfect, functional, or effective as possible. In general, optimisation is the process of obtaining either the best minimum or maximum result under specific circumstance. The optimisation process engages with defining and examining objective or fitness function that suits some parameters and constraints. Nowadays, a vast range of business, management and engineering applications utilise the optimisation approach to save time, cost and resources while gaining better profit, output, performance and efficiency